A Self‐Assembly Method‐Derived MoxC@N‐Doped Carbon Nanosheet Enabling Efficient Water Electrolysis. Issue 10 (20th March 2022) - Pan, Qinqin; Zhang, Kai; Wang, Sumin; Shen, Zhiruo; Wei, Xinyue; Wang, Qiguan
Abstract : Electrolysis of water is a promising reaction to produce the sustainable energy of hydrogen that proceeds commonly by assistance of a highly efficient catalyst. Now, the development of highly efficient and low‐cost electrocatalysts has stimulated increasing interest. Herein, a new composited electrocatalyst of Mo x C embedded in N‐doped carbon nanosheets (Mo x C@NCS) is successfully prepared from a self‐assembly route. Due to the expanded interlayers of carbon NCS and enhanced active defective sites induced by two‐materials compositing, the as‐synthesized Mo x C@NCS affords splendid hydrogen evolution reaction (HER, overpotential of 160 mV), as well as remarkable oxygen evolution reaction (OER, overpotential of 360 mV) at 10 mA cm −2 in alkaline water splitting. In view of earlier excellent performances, the bifunctional Mo x C@NCS catalyst shows a low cell voltage of 1.56 V at 10 mA cm −2 in overall water splitting. In addition, the Mo x C@NCS exhibits an outstanding stability after long‐term electrochemical measurements. These findings extend the potential application of carbon‐supported non‐noble metallic catalysts, being of great significance in sustainable energy‐related fields. Abstract : A new electrocatalyst of Mo x C embedded in N‐doped carbon nanosheets (Mo x C@NCS) is prepared from a self‐assembly route. Due to the expanded interlayers of carbon nanosheets and enhanced active defective sites induced by compositing, the Mo x C@NCS affords splendid HER overpotential of 160 mV and OER overpotential of 360 mV at 10 mA cm −2 in water splitting, showing good application prospect.